2019
DOI: 10.1007/s00236-019-00337-7
|View full text |Cite|
|
Sign up to set email alerts
|

Expressiveness of component-based frameworks: a study of the expressiveness of BIP

Abstract: We extend our previous algebraic formalisation of the notion of component-based framework in order to formally define two forms-strong and weak-of the notion of full expressiveness and study their properties. Our earlier result shows that the BIP (Behaviour-Interaction-Priority) framework does not possess the strong full expressiveness with respect to the sub-class of GSOS rules used for the definition of its semantics. In this paper we refine this comparison detailing the expressiveness of classical BIP, Offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The composition can alter the non-deterministic behaviour by suitable priority models. In [2,1] it is shown that, under mild hypothesis, priority models do not spoil deadlock freedom. This requires to compromise on expressiveness.…”
Section: Related and Future Workmentioning
confidence: 99%
“…The composition can alter the non-deterministic behaviour by suitable priority models. In [2,1] it is shown that, under mild hypothesis, priority models do not spoil deadlock freedom. This requires to compromise on expressiveness.…”
Section: Related and Future Workmentioning
confidence: 99%